Efektivitas Model Problem Based Learning dalam Pembelajaran Fisika Terhadap Motivasi Belajar Siswa pada Materi Tekanan Hidrostatis : The Effectiveness of the Problem Based Learning Model in Physics Instruction on Students’ Learning Motivation in the Topic of Hydrostatic Pressure - Anam, M. Khairil; Syahidi, Khairus; Novianti, Baiq Aryani (Lembaga Bale Literasi, 2025)
This study aimed to investigate the effect of Problem Based Learning (PBL) on students’ motivation in learning physics, particularly on the topic of hydrostatic pressure. A quasi-experimental design with nonequivalent control group was employed, involving 62 students of grade 12 at SMA Negeri 1 Lenek, divided into experimental and control groups (31 students each). The experimental class was taught using the PBL model, while the control class used conventional methods. The research instrument was a student motivation questionnaire consisting of 25 items, tested for validity and reliability. Data analysis included descriptive statistics, normality test, homogeneity test, and hypothesis testing using a t-test. The results showed that the experimental class achieved a higher mean motivation score (M = 78.62, SD = 7.79) compared to the control class (M = 53.68, SD = 7.96). The normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The t-test result (t = 12.65, p < 0.05) confirmed that PBL had a significant positive effect on students’ learning motivation. These findings suggest that PBL can be effectively implemented in physics learning to foster students’ engagement, motivation, and understanding of abstract concepts such as hydrostatic pressure.